Nephritic syndrome following multiple bee stings: a late hypersensitivity reaction. (13th May 2015) - Nag, Shankha Subhra; Ghosh, Nilanjan; Singh, Arvind Kumar; Nayek, Kaustav; Mitra, Piyali
<x content-type="archive" xml:space="preserve">Abstract</x> Most hypersensitivity reactions to insect stings are immediate, ranging from transient local reactions of little medical consequence to fatal anaphylaxis. Rarely, some patients have delayed reactions after a period of apparent normality which manifest as systemic features which can be life-threatening. A 3-year-old boy was attacked by a swarm of bees, estimated to be about 200 in number. There was an immediate cutaneous reaction which was treated at a local hospital. After 9 days, he presented with oliguria, dark-coloured urine, pedal oedema, hypertension and acute kidney injury (AKI). He was managed conservatively with fluid restriction, control of blood pressure and peritoneal dialysis, and renal function returned to normal gradually over the following 9 days. The delayed-onset AKI and other laboratory abnormalities suggested a immune-mediated type III hypersensitivity reaction leading to renal insufficiency. After improvement of initial hypersensitivity reactions, patients with bee stings should be followed up in order to detect any late-onset complications which might be life-threatening.